No evidence of a legacy effect on survival following randomization to extended hours dialysis in the ACTIVE Dialysis trial. Issue 10 (2nd July 2020) - Smyth, Brendan; Zuo, Li; Gray, Nicholas A.; Chan, Christopher T.; de Zoysa, Janak R.; Hong, Daqing; Rogers, Kris; Wang, Jia; Cass, Alan; Gallagher, Martin; Perkovic, Vlado; Jardine, Meg; et al.
Abstract: Aim: Extended hours haemodialysis is associated with superior survival to standard hours. However, residual confounding limits the interpretation of this observation. We aimed to determine the effect of a period of extended hours dialysis on long‐term survival among participants in the ACTIVE Dialysis trial. Methods: Two‐hundred maintenance haemodialysis recipients were randomized to extended hours dialysis (median 24 h/wk) or standard hours dialysis (median 12 h/wk) for 12 months. Further pre‐specified observational follow up occurred at 24, 36 and 60 months. Vital status and modality of renal replacement therapy were ascertained. Results: Over the 5 years, 38 participants died, 30 received a renal transplant, and 6 were lost to follow up. Total weekly dialysis hours did not differ between standard and extended groups during the follow‐up period (14.1 hours [95%CI 13.4‐14.8] vs 14.8 hours [95%CI 14.1‐15.6]; P = .16). There was no difference in all‐cause mortality (hazard ratio for extended hours 0.91 [95%CI 0.48‐1.72]; P = .77). Similar results were obtained after censoring participants at transplantation, and after adjusting for potential confounding variables. Subgroup analysis did not reveal differences in treatment effect by region, dialysis setting or vintage ( P ‐interaction .51, .54, .12, respectively). Conclusion: Twelve months of extended hours dialysis did not improve long‐term survival nor affect dialysis hours after the intervention period. An urgent need remains to further define the optimal dialysis intensity across the broad range of dialysis recipients. SUMMARY AT A GLANCE: Twelve months of extended‐hour dialysis did not improve long‐term survival or affect dialysis hours after the intervention period among 200 patients. These results suggest that the optimal dialysis intensity across a broad range of dialysis recipients remains to be defined.